Inovasi melalui Learning Management System (LMS): Studi Awal di Pusat Kegiatan Belajar Masyarakat (PKBM) - Achmad Syahri; Triana Rejekiningsih; Eka Budhi Santosa (Journal on Education, 2023)
This research aims to identify the various needs of students in the Package C learning program (Paket C) related to technology-based learning platforms such as the Learning Management System (LMS). This research is an initial stage that uses a quantitative descriptive approach. The participants in this research were 35 people consisting of students or residents studying Package C (Paket C) and 2 teachers or tutors. The data collection methods used are questionnaires and interviews and the results are analyzed in the form of percentages and interviews will be analyzed descriptively. The findings from this research indicate that students have a positive view of using LMS to facilitate their learning process. They believe that an LMS can provide time flexibility that allows them to continue working and be active in other activities, while still being able to access learning materials through the LMS. It is hoped that the results of this research can become the basis for developing better learning innovations for Paket C students.